What can we do in light of the Global Risks Report 2022 s ranking of the world s greatest threats - Azizul Helmi, Sofian (2022)
Risk analysis aids in the framing of decisions, predictions, and the identification of policy gaps that must be addressed. That is why, every January, the World Economic Forum releases the Global Risks Report, which sets the tone for the year.